A Family of Fast and Memory Efficient Lock- and Wait-Free Reclamation - Nikolaev, Ruslan; Ravindran, Binoy (Proceedings of ACM on programming languages, 2024)
Historically, memory management based on lock-free reference counting was very inefficient, especially for read-dominated workloads. Thus, approaches such as epoch-based reclamation (EBR), hazard pointers (HP), or a combination thereof have received significant attention. EBR exhibits excellent performance but is blocking due to potentially unbounded memory usage. In contrast, HP are non-blocking and achieve good memory efficiency but are much slower. Moreover, HP are only lock-free in the general case. Recently, several new memory reclamation approaches such as WFE and Hyaline have been proposed. WFE achieves wait-freedom, but is less memory efficient and performs suboptimally in oversubscribed scenarios; Hyaline achieves higher performance and memory efficiency, but lacks wait-freedom. We present a family of non-blocking memory reclamation schemes, called Crystalline, that simultaneously addresses the challenges of high performance, high memory efficiency, and wait-freedom. Crystalline can guarantee complete wait-freedom even when threads are dynamically recycled, asynchronously reclaims memory in the sense that any thread can reclaim memory retired by any other thread, and ensures (an almost) balanced reclamation workload across all threads. The latter two properties result in Crystalline’s high performance and memory efficiency. Simultaneously ensuring all three properties requires overcoming unique challenges. Crystalline supports ubiquitous x86-64 and ARM64 architectures, while achieving superior throughput than prior fast schemes such as EBR as the number of threads grows. We also accentuate that many recent approaches, unlike HP, lack strict non-blocking guarantees when used with multiple data structures. By providing full wait-freedom, Crystalline addresses this problem as well.